Analysis of Class Management by Teachers to Improve Student Discipline at SDN 1 Sumber - Uripah, Siti; Putra, Nugraha Permana; Rochmah, Eliya (LPPM Institut Pendidikan Nusantara Global, 2025)
This research is motivated by the low level of student discipline in class 3B of SDN 1 Sumber, characterized by late arrival, inattention during class, and violations of class rules. The purpose of this study is to describe the planning, strategies, and impact of classroom management implemented by teachers in improving student discipline. The method used was descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. The research subjects consisted of the class 3B teacher and 25 students. The results indicate that the teacher designed a classroom management plan that took into account the students' conditions, established clear rules, and provided supportive learning resources. The strategies used included a persuasive approach, the use of rewards and punishments, and the implementation of positive discipline through role modeling and habituation. The impact of these strategies is seen in improved student discipline, both in terms of punctuality, compliance with rules, and increased participation in class. In conclusion, classroom management designed systematically and humanely by teachers can create a conducive learning environment and encourage disciplined behavior in students.